Anti-Galectin-2 Antibody Treatment Reduces Atherosclerotic Plaque Size and Alters Macrophage Polarity - Kane, Jamie; Jansen, Matthijs; Hendrix, Sebastian; Bosmans, Laura A.; Beckers, Linda; Tiel, Claudia van; Gijbels, Marion; Zelcer, Noam; Vries, Carlie J. de; von Hundelshausen, Philipp; Vervloet, Marc; Eringa, Ed; Horrevoets, Anton J.; Royen, Niels van; Lutgens, Esther (Thrombosis and Haemostasis, 2022)
Background Galectins have numerous cellular functions in immunity and inflammation. Short-term galectin-2 (Gal-2) blockade in ischemia-induced arteriogenesis shifts macrophages to an anti-inflammatory phenotype and improves perfusion. Gal-2 may also affect other macrophage-related cardiovascular diseases.Objectives This study aims to elucidate the effects of Gal-2 inhibition in atherosclerosis.Methods ApoE −/− mice were given a high-cholesterol diet (HCD) for 12 weeks. After 6 weeks of HCD, intermediate atherosclerotic plaques were present. To study the effects of anti-Gal-2 nanobody treatment on the progression of existing atherosclerosis, treatment with two llama-derived anti-Gal-2 nanobodies (clones 2H8 and 2C10), or vehicle was given for the remaining 6 weeks.Results Gal-2 inhibition reduced the progression of existing atherosclerosis. Atherosclerotic plaque area in the aortic root was decreased, especially so in mice treated with 2C10 nanobodies. This clone showed reduced atherosclerosis severity as reflected by a decrease in fibrous cap atheromas in addition to decreases in plaque size.The number of plaque resident macrophages was unchanged; however, there was a significant increase in the fraction of CD206+ macrophages. 2C10 treatment also increased plaque α-smooth muscle content, and Gal-2 may have a role in modulating the inflammatory status of smooth muscle cells. Remarkably, both treatments reduced serum cholesterol concentrations including reductions in very low-density lipoprotein, low-density lipoprotein, and high-density lipoprotein while triglyceride concentrations were unchanged.Conclusion Prolonged and frequent treatment with anti-Gal-2 nanobodies reduced plaque size, slowed plaque progression, and modified the phenotype of plaque macrophages toward an anti-inflammatory profile. These results hold promise for future macrophage modulating therapeutic interventions that promote arteriogenesis and reduce atherosclerosis.
Keywords: nanobodies; anti-inflammatory agents; atherosclerosis; galectin-2; macrophages